KONTRIBUSI TERAPI REHABILITASI KOGNITIF TERHADAP FUNGSI KOGNITIF PADA PASIEN SKIZOFRENIA - Untari, Rita; Maharso Adhi Nugroho (Tahta Media Group, 2024)
Schizophrenia is a serious mental disorder accompanied by positive and negative symptoms, cognitive disorders, mood, recklessness, and aggression. Impaired cognitive function is an inability to pay attention, memory, judgment, problem-solving, and executive abilities. One of the therapies for cognitive deficits in schizophrenia patients is Cognitive Rehabilitation therapy. The research aimed to determine whether there was a contribution of cognitive rehabilitation therapy to the cognitive function of schizophrenia patients at RSJD Dr. Arif Zainudin Surakarta. This research used a quasi-experimental non-random pretest and posttest with control group design, data analysis used the comparative Wilcoxon test and the Mann-Whitney test. The sample consisted of 32 people (15 control group, 17 intervention group)—the instrument used by the Indonesian version of MoCA. The intervention was carried out over 6 meetings, in groups. The cognitive function score of the control group, the pretest mean was 20.26 and the posttest mean was 21.60. The cognitive function score of the intervention group, the average pretest score was 21.8, and the average post-test score was 25.6. The results of the pretest and posttest Wilcoxon test data analysis for the control group with sig. 0.000 with a p-value <0.05; pretest and posttest Wilcoxon test in the intervention group with sig. 0.000 and p-value <0.05; Mann-Whitney test in the control-intervention group with sig. 000 with a p-value <0.05. This indicates that there is a significant difference in cognitive function abilities between the control group and the intervention group that underwent cognitive rehabilitation therapy for schizophrenia patients at RSJD Dr. Arif Zainudin Surakarta. There was a significant difference in scores between the control group and the intervention group. The results of comparative tests between the two groups showed that there was a significant effect of cognitive rehabilitation therapy on the cognitive function of schizophrenia patients.